Vocational skill development through BRAC skill development program in Bangladesh: how this Is influencing socio-economic life of female training graduates - Ahmad, Tasnuva (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2021.